Centralización de la administración de usuarios en un centro de cómputo (2015)
The IT Laboratory currently has a computational platform composed of servers and stations with Linux, Windows and OS X operating systems, each with independent user administration which generates more administrative wear and difficulties for users in their recall and management , for this reason we want to implement a centralized authentication system where all users and systems are directed and it is he who authorizes the entry into the infrastructure of the Laboratory according to the profile of each one.